Falls risk screening tools intended to reduce fall risk among independent community-dwelling older adults: A systematic review - Mei, Fong Ong; Kim, Lam Soh; Saimon, Rosalia; Myint, Wai Wai; Pawi, Saloma; Saidi, Hasni Idayu (Wiley, 2022)
Aims The aim of this study is to evaluate an evidence-based fall risk screening tool to predict the risk of falls suitable for independent community-dwelling older adults guided by the World Health Organization's International Classification of Functioning, Disability and Health (WHO-ICF) components, and to examine the reliability and validity of the fall risk screening tool to predict fall risks, and to examine the feasibility of tools among independent community-dwelling older adults.